2014
DOI: 10.1534/g3.114.012922
|View full text |Cite
|
Sign up to set email alerts
|

Structures of Naturally Evolved CUP1 Tandem Arrays in Yeast Indicate That These Arrays Are Generated by Unequal Nonhomologous Recombination

Abstract: An important issue in genome evolution is the mechanism by which tandem duplications are generated from single-copy genes. In the yeast Saccharomyces cerevisiae, most strains contain tandemly duplicated copies of CUP1, a gene that encodes a copper-binding metallothionein. By screening 101 natural isolates of S. cerevisiae, we identified five different types of CUP1-containing repeats, as well as strains that only had one copy of CUP1. A comparison of the DNA sequences of these strains indicates that the CUP1 t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
59
2

Year Published

2014
2014
2020
2020

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 49 publications
(67 citation statements)
references
References 39 publications
6
59
2
Order By: Relevance
“…Relative to the three control genes, the BMN lines had an average of 18.13 copies of CUP1 (range: 12.40-30.45). Note that although the S288C reference genome on the SGD reports only two CUP1 copies, an isolate of S288C was recently found to contain $14 copies by Southern analysis (Zhao et al 2014). Our data are thus consistent with our ancestral BY4741 strain having undergone amplification in this region, and we report the number of CUP1 copies in our copper adaptation strains relative to the average across the BMN lines.…”
supporting
confidence: 86%
See 1 more Smart Citation
“…Relative to the three control genes, the BMN lines had an average of 18.13 copies of CUP1 (range: 12.40-30.45). Note that although the S288C reference genome on the SGD reports only two CUP1 copies, an isolate of S288C was recently found to contain $14 copies by Southern analysis (Zhao et al 2014). Our data are thus consistent with our ancestral BY4741 strain having undergone amplification in this region, and we report the number of CUP1 copies in our copper adaptation strains relative to the average across the BMN lines.…”
supporting
confidence: 86%
“…Indeed, Covo et al (2014) recently demonstrated that moving CUP1 onto other chromosomes can efficiently select for disomy under copper stress. The number of CUP1 copies varies among naturally isolated wild and vineyard strains (between 1 and 18 copies among 14 wild strains, Zhao et al 2014, and 4 and 18 copies among 15 Italian vineyard strains, Stroobants et al 2008). As CUP1 is present in the ancestral genome as a tandem repeat, it is likely prone to alterations in copy number as a consequence of unequal crossover, gene conversion, or single-strand annealing (Zhang et al 2013).…”
Section: Discussionmentioning
confidence: 99%
“…2; Supplemental Tables S5, S14). Similarly, CUP1 copy number has been precisely determined in very few strains (Fogel and Welch 1982;Hamer et al 1985;Zhao et al 2014). Based on CUP1 sequence coverage relative to flanking single-copy sequences, CUP1 copy number in the 93 strains varied from one copy (28 strains) to 18 copies (Supplemental Table S15).…”
Section: Genome Sequence Data Defines Multiple Types Of Genetic Variamentioning
confidence: 99%
“…In a survey of 100 different S. cerevisiae strains, about twothirds have tandem arrays of CUP1 repeats (21,22). Strain DZ12 has about 16 copies of CUP1, with 12 copies on the W303-1A-derived homolog and 4 on the YJM789 homolog (Fig.…”
Section: Association Of Loh Events With Elements Of Chromosome Sequenmentioning
confidence: 99%